Electroencephalographic Brain Dynamics of Memory Encoding in Emotionally Arousing Context - Uribe, Carlos Enrique; Garcia, Ana; Tomaz, Carlos Alberto B. (Frontiers in Behavioral Neuroscience, 2011)
Emotional content/context enhances declarative memory through modulation of encoding and retrieval mechanisms. At encoding, neurophysiological data have consistently demonstrated the subsequent memory effect in theta and gamma oscillations. Yet, the existing studies were focused on the emotional content effect and let the emotional context effect unexplored. We hypothesized that theta and gamma oscillations show higher evoked/induced activity during the encoding of visual stimuli when delivered in an emotionally arousing context. Twenty-five healthy volunteers underwent evoked potentials recordings using a 21 scalp electrodes montage. They attended to an audiovisual test of emotional declarative memory being randomly assigned to either emotionally arousing or neutral context. Visual stimulus presentation was used as the time-locking event. Grand-averages of the evoked potentials and evoked spectral perturbations were calculated for each volunteer. Evoked potentials showed a higher negative deflection from 80 to 140 ms for the emotional condition. Such effect was observed over central, frontal and prefrontal locations bilaterally. Evoked theta power was higher in left parietal, central, frontal and prefrontal electrodes from -50 to 300 ms in the emotional condition. Evoked gamma power was higher in the emotional condition with a spatial distribution that overlapped at some points with the theta topography. The early theta power increase could be related to expectancy induced by auditory information processing that facilitates visual encoding in emotional contexts. Together, our results suggest that declarative memory enhancement for both emotional content and emotional context are supported by similar neural mechanisms at encoding, and offer new evidence about the brain processing of relevant environmental stimuli.